(untitled) (Bioscience Journal, 2016)
Foliar applications of calcium (Ca) and boron (B) could improve the fertilization of flowers and enhance the wheat yield. The effects of foliar spray of Ca and B on plant growth, grain yield and yield components of wheat were investigated in this study. Treatments consisted of 0, 1.8, 3.6, and 7.2 L ha-1 application of chelated fertilizer containing 125 g L-1 of Ca and 6 g L-1 of B (Omega Cabor II®), divided into two spray, the first one at tillering and the second at early bloom. The results revealed that foliar spray of Ca and B did not affect the stem diameter, peduncle length, spike length, hectoliter weight and thousand-grain mass of wheat. Maximum plant height and flag leaf insertion height was recorded with 4.0 L ha-1 application of foliar fertilizer (4% increase over control). The 7.2 L ha-1 application of foliar fertilizer increased significantly the number of spikelets per spike (9%), number of grains per spike (24%), grain mass per spike (28%), spike mass (14%), number of spikes m-2 (32%) and grain yield (30%) compared to the control. Foliar application of Ca and B improves growth, fertilization of flowers and the number of fertile tillers of wheat plants resulting in higher grain yield.